2018
DOI: 10.3390/coatings8020057
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Sol-Gel Silica Antireflective Coatings by F-PMHS: A Simple Method for Improvement of Amphiphobicity

Abstract: Sol-gel silica antireflective coatings (ARCs) with improved amphiphobicity were simply fabricated on BK7 glass substrates via fluorinated-poly(methylhydrogen)siloxane (F-PMHS) surface modification by the dip-coating method. The results of Fourier Transform Infrared (FTIR) and X-ray Photoelectron Spectroscopy (XPS) showed that F-PMHS were covalently bonded to the surface of ARCs. F-PMHS modification significantly improved hydrophobicity and oleophobicity of silica ARCs by increasing their water contact angles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…They demonstrated that the antifogging and transparency properties were due to the low water contact angles and the decrease of refractive index, respectively. Lin et al [11] realized sol-gel silica antireflective coatings with amphiphobic property and good transmittance. Gao et al [12] fabricated antireflective superhydrophobic coatings using three silica-based sols: silica sol prepared in acidic medium, silica nanoparticle suspension prepared according to the Stöber method and mesoporous silica nanoparticle suspension, followed by chemical vapor deposition of 1H,1H,2H,2H-perfluorooctyltriethoxysilane.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the antifogging and transparency properties were due to the low water contact angles and the decrease of refractive index, respectively. Lin et al [11] realized sol-gel silica antireflective coatings with amphiphobic property and good transmittance. Gao et al [12] fabricated antireflective superhydrophobic coatings using three silica-based sols: silica sol prepared in acidic medium, silica nanoparticle suspension prepared according to the Stöber method and mesoporous silica nanoparticle suspension, followed by chemical vapor deposition of 1H,1H,2H,2H-perfluorooctyltriethoxysilane.…”
Section: Introductionmentioning
confidence: 99%
“…With Karstedt catalyst, the addition reaction between -Si-H of PMHS-modified cotton fabric and vinyl groups of 1H,1H,2H-perfluoro-1-decene occurs easily at room temperature, and therefore, the long fluoroalkyl chains can be grafted onto the cotton fabrics by a simple immerging method. As shown in XPS spectra (Figure 2e), there was an addition peak at 689.19 eV attributed to the F element [64]. As shown in Figure 6, as the oil droplet (about 0.05 mL) was dripped onto pristine cotton fabric, the oil spread easily, and quite a big area of cotton fabric was stained by oil.…”
Section: Application In Stain-resistancementioning
confidence: 91%
“…In addition, the coating showed an excellent transmittance due to the formation of convex with irregular shapes that increased the porosity. Different from the two studies, Lin et al (2018) [10], used a fluorinated-PMHS (F-PMHS). The optimized result showed a 115° WCA and 99.5% transmittance.…”
Section: Polymethylhydrosiloxane (Pmhs)mentioning
confidence: 99%